Effects of early tooth loss on chronic stress and progression of neuropathogenesis of Alzheimer’s disease in adult Alzheimer’s model AppNL-G-F mice - Ochi, Suzuko; Yamada, Kumiko; Saito, Takashi; Saido, Takaomi C.; Iinuma, Mitsuo; Azuma, Kagaku; Kubo, Kin-Ya (Frontiers in Aging Neuroscience, 2024)
Alzheimer's disease (AD), the most common neurodegenerative disease, is characterized by accumulated amyloid-β (Aβ) plaques, aggregated phosphorylated tau protein, gliosis-associated neuroinflammation, synaptic dysfunction, and cognitive impairment. Many cohort studies indicate that tooth loss is a risk factor for AD. The detailed mechanisms underlying the association between AD and tooth loss, however, are not yet fully understood. We explored the involvement of early tooth loss in the neuropathogenesis of the adult App NL-G-F mouse AD model. The maxillary molars were extracted bilaterally in 1-month-old male mice soon after tooth eruption. Plasma corticosterone levels were increased and spatial learning memory was impaired in these mice at 6 months of age. The cerebral cortex and hippocampus of AD mice with extracted teeth showed an increased accumulation of Aβ plaques and phosphorylated tau proteins, and increased secretion of the proinflammatory cytokines, including interleukin 1β (IL-1β) and tumor necrosis factor α (TNF-α), accompanied by an increased number of microglia and astrocytes, and decreased synaptophysin expression. AD mice with extracted teeth also had a shorter lifespan than the control mice. These findings revealed that long-term tooth loss is a chronic stressor, activating the recruitment of microglia and astrocytes; exacerbating neuroinflammation, Aβ deposition, phosphorylated tau accumulation, and synaptic dysfunction; and leading to spatial learning and memory impairments in AD model mice.